2015
DOI: 10.4236/wja.2015.54033
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Asymptomatic Bacteriuria and HIV-1 Viral Load Level and CD4 Count in Pregnant Women on Antiretroviral Therapy in N’djamena (Chad)

Abstract: A cross-sectional study was conducted at the "Centre de l'Appui Psycho-Médico-Social (APMS)" which is a centre for Psychological and Medical Support in N'Djamena (Chad) from January to March 2014. The aim of this study was to evaluate the correlation between asymptomatic bacteriuria (ASB) and viral load level and CD4 count in seventy-six (76) HIV-1 infected pregnant women on antiretroviral therapy (ART). Urine culture and bacteria identification were performed by using a chromogenic culture medium (UriselectR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…With respect to CD4+ T-cell counts, patients with less than 300cells/mm 3 where more predisposed to UTIs than those who had counts greater than 500cells/mm 3 . This correlates with other studies carried out earlier in the same hospital 5 , and other studies in Tchad 19 , Ethiopia 15 , Bangalore and the Netherlands 14,20 . No relationship, has however, been shown to exist between bacteriuria and CD4+ T-cell counts among HIV-seropositive patients by several other studies carried out in different countries 6,[21][22] .…”
Section: Discussionsupporting
confidence: 92%
“…With respect to CD4+ T-cell counts, patients with less than 300cells/mm 3 where more predisposed to UTIs than those who had counts greater than 500cells/mm 3 . This correlates with other studies carried out earlier in the same hospital 5 , and other studies in Tchad 19 , Ethiopia 15 , Bangalore and the Netherlands 14,20 . No relationship, has however, been shown to exist between bacteriuria and CD4+ T-cell counts among HIV-seropositive patients by several other studies carried out in different countries 6,[21][22] .…”
Section: Discussionsupporting
confidence: 92%
“…In current study, bacterial uropathogens were mainly isolated from HIV patients with a CD4 count of >200 cells/ml. This finding was corroborated with other study conducted in Chad (Abderrazzack et al, 2015 ). There was a significant relationship between CD4+ cell count and UTI ( p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a study in Nigeria noticed that bacteriuria in HIV-infected women was not affected by CD4 counts [37], bacteriuria was not affected by CD4 counts of less than 200 cells/mm 3 [38], and CD4 cell counts of <200 cells/mm 3 does not affect the occurrence of asymptomatic bacteriuria [39]. Other studies yielded different results in that bacteriuria was found to correlate to CD4 cell counts and/or viral loads [40][41][42]. Bacteriuria may not be affected by CD4 counts because research shows that immunity to UTIs results from complex interactions between host factors and the invading organism.…”
Section: Analysis Of the Correlation Between The Cd4 Counts And The P...mentioning
confidence: 99%